Treaty on the Prohibition Of Nuclear Weapons (TPNW): Stigmatisation, Normative Impact and Discursive Approach (Journal of Contemporary Studies, 2025)
This paper explores the underlying efforts of the international anti nuclear movement, specifically the Humanitarian Initiative led by Non-Nuclear Weapon States and supported by the International Campaign to Abolish Nuclear Weapons (ICAN), seeking to further the cause of nuclear disarmament. The movement was successful in finalizing the Treaty on the Prohibition of Nuclear Weapons (TPNW) in 2017 at the UN General Assembly with a vote of 122 in favor. Remarkably, the treaty entered into force in 2021 comprehensively outlaws the development, testing, transferring, receiving, keeping, using or threatening the use of nuclear weapons. The advocates of the treaty urge that nuclear weapons are the most inhumane and indiscriminate weapons that inflict damage on a mass scale. Their potential use violates international humanitarian and human rights laws and may cause significant environmental damage. Based on these assumptions, they argue that nuclear  weapons must be eliminated urgently. The paper underscores the discussions of ‘stigmatization’ and ‘devaluing’ of nuclear weapons, ‘normative impact’ of the treaty, and ‘discursive approach’ through reframing of the debates. The research uses qualitative methodology and utilizes content analysis of open source data for analysis.